Optical coherence tomography angiography of the eye - Huang, David; Lumbroso, Bruno; Jia, Yali, 1978-; Waheed, Nadia K. (SLACK Incorporated, 2017)
Inside Optical Coherence Tomography Angiography of the Eye Drs. David Huang, Bruno Lumbroso, Yali Jia, and Nadia Waheed include detailed information on clinical applications and fundamental principles needed to understand and use this new technology. This includes information on high-speed OCT systems, algorithms to extract flow contrast, the appearance of the normal eye, the findings in myriad diseases, and tips on how to deal with artifact and pitfalls.